Distinct Patterns of Choroidal Lesions in Punctate Inner Choroidopathy and Multifocal Choroiditis Determined by Heatmap Analysis. (17th February 2022) - Park, Jong G.; Halim, Muhammad Sohail; Uludag, Gunay; Onghanseng, Neil; Sredar, Nripun; Sepah, Yasir J.; Nguyen, Quan Dong
ABSTRACT: Purpose: A heatmap analysis of choroidal lesions in patients with punctate inner choroidopathy (PIC) or multifocal choroiditis (MFC) with or without uveitis was performed to determine if there were any distinguishing features among these uveitic entities. Methods: Retrospective review of medical records was conducted at the Byers Eye Institute, Stanford. Fundus photographs were masked and placed on a standardized template. Lesions were identified and heatmaps were generated in a standardized fashion. Results: 30 eyes were identified with PIC or MFC. Heatmap analysis revealed three distinct patterns of fundus lesions: posterior, peripheral, and combined. All patients with PIC had the posterior pattern. Patients with MFC had the peripheral or combined pattern, and all patients with MFC with uveitis had the combined pattern. Conclusion: Three patterns of fundus lesions were identified in patients with PIC and MFC. PIC and MFC may represent two separate disease entities with distinct phenotypes of choroidal lesions.